The politics of hunger : protest, poverty and policy in England, c. 1750-c. 1840 - Griffin, Carl J. (Carl James) (Manchester University Press, 2020)
Systematically explores what it is conceived as 'hunger politics': the articulations of hunger as a tool of protest by poor consumers; its framing as a problem in the making of public policy; and its (elite) political languages and the attendant effects.